2017
DOI: 10.1039/c7ra11117g
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mono-lithium based initiators with different steric volumes on 1,4 unit content of hydroxyl terminated polybutadiene using anionic polymerization

Abstract: The influence of steric structural factors of mono-lithium based anionic initiators on 1,4 unit content of hydroxyl terminated polybutadiene was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…It is well-known that the higher the content of cis -1,4 structure in the molecular chain of HTPB, the lower the T g and the better the low-temperature resistance (good mechanical properties in the low-temperature environment). , For example, the cis -1,4 structure in polybutadiene rubber prepared by coordination polymerization is as high as 98%, and its T g is as low as −108 °C, which is more than 40 °C lower than that of conventional HTPB. Due to the limitation of the free radical polymerization reaction mechanism, the proportion of cis -1,4 structure in the molecular structure of conventional HTPB can only reach about 20%. , In order to further increase the content of cis -1,4 structure, researchers prepared HTPB by anionic polymerization, coordination polymerization, and ring-opening complex decomposition polymerization, respectively. Unfortunately, these preparation methods not only require complex catalytic processes and high production costs but also the content of cis -1,4 structure is still difficult to reach more than 90%.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the higher the content of cis -1,4 structure in the molecular chain of HTPB, the lower the T g and the better the low-temperature resistance (good mechanical properties in the low-temperature environment). , For example, the cis -1,4 structure in polybutadiene rubber prepared by coordination polymerization is as high as 98%, and its T g is as low as −108 °C, which is more than 40 °C lower than that of conventional HTPB. Due to the limitation of the free radical polymerization reaction mechanism, the proportion of cis -1,4 structure in the molecular structure of conventional HTPB can only reach about 20%. , In order to further increase the content of cis -1,4 structure, researchers prepared HTPB by anionic polymerization, coordination polymerization, and ring-opening complex decomposition polymerization, respectively. Unfortunately, these preparation methods not only require complex catalytic processes and high production costs but also the content of cis -1,4 structure is still difficult to reach more than 90%.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that the different microstructures of HTPB have a great influence on its own properties, and the mechanism of its influence may be explored through a reasonable molecular simulation [ 21 ]. At present, there are three main methods for the polymerization of HTPB, namely, free radical polymerization [ 22 , 23 ], anionic polymerization [ 24 , 25 , 26 ], and ring-opening metathesis polymerization (ROMP) [ 27 , 28 ]. In a previous study, our group reported in detail the differences in the structures and properties of HTPB prepared via the three polymerization methods.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Telechelic polymers have special functional groups and can be prepared using anionic polymerization, which enables using functional SBR as the SS of polyurethane via anionic polymerization. [20] Benvenuta-Tapia et al [21] adjusted the T g of SBR from −60 to −15 °C by controlling the styrene content. Lee et al [22] successfully prepared block copolymers of styrene isoprene styrene (SIS) and styrene isoprene styrene (ISI) with different vinyl content by adjusting the reaction temperature and polarity-modifier dosage.…”
Section: Introductionmentioning
confidence: 99%